2022
DOI: 10.1177/18479804221106321
|View full text |Cite
|
Sign up to set email alerts
|

Development of graphitic carbon nitride supported novel nanocomposites for green and efficient oxidative desulfurization of fuel oil

Abstract: The catalysts utilized for oxidative desulfurization have acquired significant attention and ability to improve the quality of the fuel oil by removing sulfur. In this work, the catalysts used for oxidative desulfurization include CoWO4 and Bi2WO6 with graphitic carbon nitride (g-C3N4) as support were synthesized by the one-pot hydrothermal method. Graphitic carbon nitride was obtained by thermal polycondensation of melamine at 550°C for 5 h. These catalysts were homogeneously dispersed on the surface of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…They significantly improve their adsorption capacity and develop strong interaction between the extracting substance and the DcILs in comparison to monocationic ILs. 25 Keeping these aspects in view and in continuation to our previous work, [26][27][28] five DcILs have been synthesized and exploited as catalysts in the extraction and catalytic oxidative desulfurization (ECODS) procedure using hydrogen peroxide as an oxidizing agent. The data revealed that the combined effects of extractive and catalytic functions of the synthesized DcILs have been established and found to be an efficient and costeffective method for the oxidative desulfurization process.…”
Section: Introductionmentioning
confidence: 94%
“…They significantly improve their adsorption capacity and develop strong interaction between the extracting substance and the DcILs in comparison to monocationic ILs. 25 Keeping these aspects in view and in continuation to our previous work, [26][27][28] five DcILs have been synthesized and exploited as catalysts in the extraction and catalytic oxidative desulfurization (ECODS) procedure using hydrogen peroxide as an oxidizing agent. The data revealed that the combined effects of extractive and catalytic functions of the synthesized DcILs have been established and found to be an efficient and costeffective method for the oxidative desulfurization process.…”
Section: Introductionmentioning
confidence: 94%
“…[ 35 ] Similarly, for ODS various metal‐based catalysts such as metal oxides, metal oxides supported on various supports like macroporous polyacrylic cationic exchange resins, graphitic carbon nitride and graphene oxides, metal complexes, POMs, ionic liquids (ILs), titanosilicates, fenton and fenton‐like catalyst and MOFs are reported. [ 36–41 ]…”
Section: Introductionmentioning
confidence: 99%
“…[35] Similarly, for ODS various metalbased catalysts such as metal oxides, metal oxides supported on various supports like macroporous polyacrylic cationic exchange resins, graphitic carbon nitride and graphene oxides, metal complexes, POMs, ionic liquids (ILs), titanosilicates, fenton and fenton-like catalyst and MOFs are reported. [36][37][38][39][40][41] Metal-organic framework (MOF) as a modern, stateof-the-art and emerging class of porous crystal materials have been comprehensively explored because of their facile and reticular synthesis and several prospective applications. They are known as coordination polymers and are obtained by connecting cluster units or metal cations to multitopic organic moieties called as linkers through coordinate or weak covalent bonding to form 3D network.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of literature has been published for photodegradation of dyes and organic pollutants. [20][21][22][23][24][25][26] However, there are limited studies on zirconia-based composites for photodegradation of dyes. Regarding the overhead remarks, this study comprises the synthesis of Fe-and Nidoped ZrO 2 materials and their performance for the first time for photodegradation of MB, MG, and mixtures of dyes.…”
Section: Introductionmentioning
confidence: 99%